History and Characteristics of the Arab Village Settlement Al-Munawar 13 Ulu, Palembang, South Sumatra - Asysyauki, Akhmad Hamdi; Ardiyanto, Antonius (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Palembang, with the beauty of the Musi River flowing through its city center, serves as a central point in the community's life. The city of Palembang is divided into two regions, namely Seberang Ulu (Ulu) and Seberang Ilir (Ilir), separated by the Musi River since the era of the Palembang Sultanate. The Arab ethnic community in Palembang is concentrated in several villages, one of which is Arabian Village Al-Munawar 13 Ulu Palembang, a settlement of the descendants of Habib Abdurrahman or Abdullah Al- Munawar who settled from Hadhramaut. They adhere strictly to the practice of marrying within the Arab lineage and reside along the banks of the Musi River. This village holds the potential for development but also requires preservation to prevent possible displacement in the future. The village's houses encompass various forms, including